2014
DOI: 10.1002/lt.23903
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in liver transplant recipients: Experience of a South Indian liver transplant center

Abstract: Tuberculosis (TB) is a serious disease for liver transplant recipients (LTRs). Data on post-liver transplant TB from high-burden countries are scant. The aims of this study were to describe the prevalence of TB in LTRs from a high-prevalence area and to analyze the risk factors for the development of post-liver transplant TB. We performed a retrospective review of our database and a case-control study of identified cases with TB and age-matched LTRs without TB. The overall prevalence of TB in LTRs was comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…The median age was 45 (range 31‐64) and 49 (range, 19‐74) years among cohorts and case reports, respectively. Twenty‐one studies calculated mean age of 39.44 years (range, 24.2‐54.4). Most patients were male (1301/2073 [62.76%]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median age was 45 (range 31‐64) and 49 (range, 19‐74) years among cohorts and case reports, respectively. Twenty‐one studies calculated mean age of 39.44 years (range, 24.2‐54.4). Most patients were male (1301/2073 [62.76%]).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 253 TB cases among liver recipients were reported in 20 cohort studies and 22 case reports . Of these, 78 of 106 cases (73.58%) were male.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been noted that alfa feto protein is usually not elevated when cumulative tumor size is smaller. 25 An earlier study from our center had shown that there was a low prevalence of TB in postliver transplant recipients. However, recurrence is rare in those with incidentally detected HCC.…”
Section: Discussionmentioning
confidence: 83%